2017
DOI: 10.3390/s17112642
|View full text |Cite
|
Sign up to set email alerts
|

Fast, Low-Cost and Non-Destructive Physico-Chemical Analysis of Virgin Olive Oils Using Near-Infrared Reflectance Spectroscopy

Abstract: Near-Infrared (NIR) Spectroscopy was used for the non-destructive assessment of physico-chemical quality parameters in olive oil. At the same time, the influence of the sample presentation mode (spinning versus static cup) was evaluated using two spectrophotometers with similar optical characteristics. A total of 478 olive oil samples were used to develop calibration models, testing various spectral signal pre-treatments. The models obtained by applying MPLS regression to spectroscopic data yielded promising r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
33
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 25 publications
5
33
1
Order By: Relevance
“…Comparison with results obtained from different ring tests underline the performance of the presented approach ( z ‐scores between −0.8 and 0.9) (Table ). Garrido et al using the previously mentioned set of oils reported an RMSEP very similar (0.06%) to the one obtained in this work.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…Comparison with results obtained from different ring tests underline the performance of the presented approach ( z ‐scores between −0.8 and 0.9) (Table ). Garrido et al using the previously mentioned set of oils reported an RMSEP very similar (0.06%) to the one obtained in this work.…”
Section: Resultssupporting
confidence: 88%
“…Different proficiency tests resulted in good z ‐scores confirming the accuracy of the NIR‐method (Table ). Garrido et al using a set of n = 359 and n = 100 olive oils for calibration and validation reported a RMSEP of 1.31, slightly higher than the one obtained here.…”
Section: Resultscontrasting
confidence: 74%
See 2 more Smart Citations
“…Despite this progress, little research has been done into the in situ analysis of large volumes of olive oils in bulk using near infrared spectroscopy (NIRS). 9,10 For this reason, work has been carried out within the framework of a research project at the Department of Agrolivestock Systems Engineering (University of Córdoba, Spain) to design and build a fiber-optic probe. This tool, interfaced to a NIRS instrument, could serve to sample and analyse olive oils directly in the tanker trucks.…”
Section: Introductionmentioning
confidence: 99%